Delays in seeking healthcare and its determinants among malaria patients in Ethiopia: A systematic review and meta-analysis - Moges Tadesse Abebe; Tesfahun Zemene Tafere; Kaleab Tesfaye Tegegne; Dessie Alemnew Shiferaw; Yosef Aragaw Gonete; Tadele Kassahun Wudu; Getnet Azanaw Takele; Muluken Chanie Agimas (PLoS ONE, 2025)
Delays in seeking healthcare among malaria patients are typically associated with an increased risk of severe disease and mortality. Determining the pooled prevalence and determinants of delays in seeking healthcare may help reduce morbidity and mortality. Therefore, the aim of this systematic review and meta-analysis was to determine the pooled prevalence of delays in seeking healthcare and its determinants among malaria patients in Ethiopia. Methods PubMed, Cochrane Library, Scopus, Web of Science, Google Scholar and Google were searched. Cross-sectional and case–control studies about delays in seeking healthcare for more than 24 hours were included. STATA 17 was used to analyze the data. Heterogeneity across studies was assessed via the I2 test. A funnel plot and Egger’s test were used to assess publication bias. Subgroup analyses were performed by region and study setting. Sensitivity analysis was performed to determine the influence of individual studies. Results A total of 18 articles with 7371 participants were included in this review. The pooled prevalence of delay in seeking healthcare was 67% (95% CI: 51%-84%). Age less than 15 years (OR: 2.27, 95% CI: 1.34-3.85), inability to read and write (OR: 3.36, 95% CI: 1.18-9.69), travel to health institutions on foot (OR: 2.77, 95% CI: 1.71-4.49), and by horse (OR: 2.76, 95% CI: 1.57-4.84), living far from a health institution (OR: 2.65, CI: 1.37-5.13), not having a family history of death (OR: 3.04, 95% CI: 2.14-4.33), and not being a member of community-based health insurance (OR: 7.14, 95% CI: 1.09-46.63) were significant determinants of delays in seeking healthcare. Conclusion The pooled prevalence of delays in seeking healthcare was high, and most of the determinants were modifiable. These findings underscore the need for targeted interventions to address these barriers and improve timely access to healthcare for affected populations.